Peningkatan Pengetahuan Guru PAUD tentang Kesehatan Gizi Anak melalui Pameran Menu Gizi - Sofyan, Muhammad Kharizmi; Fauziatul Halim; Novysa Basri; Rudi Juli Saputra; Sari Rizki; Rahma; Afkar (LPPM UNINUS, 2024)
Community service activities (CSA) are activities that aim to help certain communities in several activities that are useful for increasing community knowledge, insight, and skills in a matter or field. PkM is one part of the Tri Dharma of Higher Education, an educational activity in the community in the form of non-formal education for people involved in the world of education and the general public. The PkM implemented by this team is a forum for activities for teachers and prospective Early Childhood Education teachers to increase and expand their knowledge about child nutrition because child nutrition is an important factor in supporting optimal early childhood development. Because nutrition and early childhood education are closely related, a childhood teacher must know this knowledge not only about children's health but also in line with the integration of the national PAUD program, namely integrative holistic PAUD. The integration of PAUD knowledge with health and nutrition will provide new knowledge for PAUD teachers to find out more about the influence of children's learning development on whether children's health and nutrition are good or not when displaying the nutrition menu. Childhood teachers are asked to follow cooking instructions by preparing tools and ingredients in a healthy nutrition and toddler menu book. Six cooking groups are participating and each group consists of four PAUD teachers and childhood department students, who will then cook food with a nutritional menu and present it. nutritional menu contained in the composition of cooked food. This performance was held at Almuslim University (Umuslim) Bireuen, inviting twelve PAUD teachers from six PAUD schools in Bireuen Regency. Keywords: Early Childhood, Exhibition, Healthy, Nutrition